PERANCANGAN PERHIASAN BERBAHAN KUNINGAN UNTUK PENGANTIN WANITA DENGAN INSPIRASI BUNGA KAMPERFULI - Rahmita An’nur Irawati; Dedy Ismail (Indonesian Society of Applied Science, 2022)
This paper discusses the design of jewelry for the bride, to answer the needs due to the shift in cultural values ​​in the way of dressing (outfit) at the wedding. In contrast to the traditional wedding attire, which had a 'grip' and a large number of objects, nowadays the procession and wedding accessories are carried out more simply, among others, by reducing the number or type of accessories, leaving some such as the main clothes, hair and facial makeup, and some jewelry. This change can be seen from the tendency of users to modify wedding clothes according to their character without referring to customs or cultural 'standards'. The design objective set out in this paper is to produce a jewelery design that facilitates the bride and groom against the above phenomena. This design process begins with identifying, analyzing, concluding, and then solving problems using a design by doing approach. To get the quality of the form used a visual approach by using the inspiration of Kamperfuli flowers. Kamperfuli flowers are an inspiration because they have a meaning that is in line with marriage. At the end of the process, a design work is obtained in the form of a prototype of a jewelry set that offers a novelty shape based on the stylized Kamperfuli flower.